A New and Practical Synthesis of Vortioxetine Hydrobromide - Mao, Yongjun; Jiang, Luobin; Chen, Tianyun; He, Haijun; Liu, Gang; Wang, Han (Synthesis, 2015)
A new and improved synthetic route to vortioxetine hydrobromide is established on a hectogram scale through three simple steps in 63% yield and with 99% purity (HPLC). The key step is the cyclization of the piperazine ring in the final step. Purification methods for the intermediates involved in the route are given.
Keywords: vortioxetine hydrobromide; new route; synthetic process; atypical antidepressant; green chemistry